Exploring the Impact of Entrepreneurial and Market Orientation on Marketing Performance: The Mediating Role of Product Innovation in Rattan Craftsmanship - Syuhud, Fikrotus; Komariyatin, Nurul (Golden Ratio of Marketing and Applied Psychology of Business, 2025)
This study investigates the impact of entrepreneurial and market orientation on marketing performance, with product innovation as a mediating factor among rattan artisans in Jepara. Employing a quantitative approach, the research utilizes Structural Equation Modeling-Partial Least Squares (SEM-PLS) through SmartPLS 0.4. Data were gathered via questionnaires and interviews with 155 artisans, selected using the Slovin formula and purposive sampling. The findings indicate that product innovation significantly enhances the influence of entrepreneurial and market orientation on marketing performance. While entrepreneurial orientation alone does not directly improve marketing performance, its effect becomes significant when mediated by product innovation. In contrast, market orientation positively affects marketing performance both directly and indirectly. These results underscore the critical role of product innovation in aligning entrepreneurial strategies with market demands, highlighting its importance in enhancing marketing outcomes.